Pengaruh Pengungkapan Sustainability Reporting Terhadap Profitabilitas Dan Dampaknya Pada Nilai Perusahaan - Nadia Agustin Harfiani (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
Sustainability Reporting is a sustainability report in which there is information on aspects of economic performance, social performance, and environmental performance published by a company to provide transparency to stakeholders. This study uses a quantitative method with a sample of 10 financial sector service companies, which are listed on the Indonesia Stock Exchange for the period 2014 - 2018. The sampling technique used is purposive sampling, based on certain criteria. The data used are secondary data with data analysis using panel data regression models with data processing using Eview 11 and Microsoft Office Excel. The results of this study indicate that simultaneously economic performance, social performance, and environmental performance have an effect on profitability with the coefficient of determination (RSquared) of 52.17%. Partially, economic performance, social performance, and environmental performance have a positive and significant effect on profitability. Profitability has a positive and significant effect of 65.91% on firm value.